TECHNOLOGY, AN ALLY TO THE 21ST CENTURY WOMEN: AN ESSAY - López Núñez, Vivian (International Journal of Law in Changing World, 2025)
This essay explores how digital technology serves as a powerful ally for women’s empowerment in Paraguay, particularly in the legal field. Drawing from the author’s experience as the country’s first judge to lead a fully digital court process, the text shows how technological tools help women reconcile professional and domestic responsibilities, while promoting greater access, security, and transparency in the justice system. It also highlights the persistent gender inequalities in Paraguay and argues that, while technology is not a cure-all, it can significantly reduce barriers to real equality—if implemented thoughtfully. The essay uses qualitative reflection to underscore how virtual hearings, remote work, and safety-enhancing tools like panic apps or monitoring bracelets offer concrete benefits to women. However, it also warns that unregulated algorithms risk reinforcing discrimination. The essay concludes with a call for responsible use and regulation of technology to ensure it contributes to lasting change for women in all spheres of life. _____ TECNOLOGIA, UNA ALIADA DE LAS MUJERES DEL SIGLO XXI: UN ENSAYO Este ensayo analiza cómo la tecnología digital actúa como una aliada clave para el empoderamiento de las mujeres en Paraguay, especialmente en el ámbito judicial. A partir de la experiencia de la autora como la primera jueza del país en liderar un proceso judicial completamente digital, el texto muestra cómo las herramientas tecnológicas permiten a las mujeres conciliar las responsabilidades laborales y domésticas, al tiempo que mejoran el acceso, la seguridad y la transparencia en el sistema judicial. También se aborda la persistente desigualdad de género en el país y se argumenta que, si bien la tecnología no es una solución absoluta, puede reducir significativamente las barreras hacia la igualdad real si se implementa con responsabilidad. Mediante una reflexión cualitativa, el ensayo expone los beneficios concretos de audiencias virtuales, el trabajo remoto y dispositivos de protección. Finalmente, se advierte sobre los sesgos en los algoritmos y se propone regular la tecnología para garantizar avances duraderos en los derechos de las mujeres. _____ 技术, 21世纪女性的盟友:篇随笔 本文探讨了数字技术如何成为推动巴拉圭女性赋权的重要力量，尤其在司法领域。作者作为该国首位领导全数字化法院流程的法官，分享了亲身经验，说明科技工具如何帮助女性平衡职业与家庭责任，同时提升司法系统的透明度、安全性与可及性。文章指出，尽管巴拉圭依然存在严重的性别不平等，但科技若被妥善使用，可显著减少女性在追求真正平等道路上的障碍。文章通过反思性分析强调了远程庭审、灵活办公、以及如报警App和电子监控装置等安全技术给女性带来的切实益处。然而，作者也警告，若缺乏监管，算法可能延续或加剧性别歧视。文章最后呼吁以负责任的方式使用并监管技术，使其成为女性争取权利、改善生活条件的有力工具，而非新的障碍